2013
DOI: 10.1021/jm301741t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of (R)-4-Cyclopropyl-7,8-difluoro-5-(4-(trifluoromethyl)phenylsulfonyl)-4,5-dihydro-1H-pyrazolo[4,3-c]quinoline (ELND006) and (R)-4-Cyclopropyl-8-fluoro-5-(6-(trifluoromethyl)pyridin-3-ylsulfonyl)-4,5-dihydro-2H-pyrazolo[4,3-c]quinoline (ELND007): Metabolically Stable γ-Secretase Inhibitors that Selectively Inhibit the Production of Amyloid-β over Notch

Abstract: Herein, we describe our strategy to design metabolically stable γ-secretase inhibitors which are selective for inhibition of Aβ generation over Notch. We highlight our synthetic strategy to incorporate diversity and chirality. Compounds 30 (ELND006) and 34 (ELND007) both entered human clinical trials. The in vitro and in vivo characteristics for these two compounds are described. A comparison of inhibition of Aβ generation in vivo between 30, 34, Semagacestat 41, Begacestat 42, and Avagacestat 43 in mice is ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Lipid rafts are involved in ␤-and ␥-secretase cleavage of APP (Ehehalt et al, 2003;Vetrivel and Thinakaran, 2010) and in line with our results, it has been shown that alterations in the cholesterol level influence A␤ generation (Refolo et al, 2000;Fassbender et al, 2001;Wahrle et al, 2002;Ghribi et al, 2006). As plant sterols, compared with cholesterol, have a similar sterol backbone, we analyzed whether stigmasterol affects cholesterol distribution and thus ␥-secretase activity in lipid raft membrane microdomains.…”
Section: Stigmasterol Decreases ␥-Secretase Activity By Affecting Chosupporting
confidence: 88%
See 4 more Smart Citations
“…Lipid rafts are involved in ␤-and ␥-secretase cleavage of APP (Ehehalt et al, 2003;Vetrivel and Thinakaran, 2010) and in line with our results, it has been shown that alterations in the cholesterol level influence A␤ generation (Refolo et al, 2000;Fassbender et al, 2001;Wahrle et al, 2002;Ghribi et al, 2006). As plant sterols, compared with cholesterol, have a similar sterol backbone, we analyzed whether stigmasterol affects cholesterol distribution and thus ␥-secretase activity in lipid raft membrane microdomains.…”
Section: Stigmasterol Decreases ␥-Secretase Activity By Affecting Chosupporting
confidence: 88%
“…As expected cholesterol significantly increased A␤ levels (122.4% Ϯ 1.3, p Յ 0.001) compared with the solvent control ( Fig. 2A) (Refolo et al, 2000;Fassbender et al, 2001;Refolo et al, 2001;Ghribi et al, 2006;Xiong et al, 2008). Stigmasterol strongly reduced A␤ levels (62.00% Ϯ 3.9, p ϭ 0.0005) ( Fig.…”
Section: Effect Of Plant Sterols and Cholesterol On A␤ Secretionsupporting
confidence: 67%
See 3 more Smart Citations